2019
DOI: 10.2147/copd.s219125
|View full text |Cite
|
Sign up to set email alerts
|

<p>Respiratory Mechanics and Diaphragmatic Dysfunction in COPD Patients Who Failed Non-Invasive Mechanical Ventilation</p>

Abstract: BackgroundAlthough non-invasive mechanical ventilation (NIV) is the gold standard treatment for patients with acute exacerbation of COPD (AECOPD) developing respiratory acidosis, failure rates still range from 5% to 40%. Recent studies have shown that the onset of severe diaphragmatic dysfunction (DD) during AECOPD increases risk of NIV failure and mortality in this subset of patients. Although the imbalance between the load and the contractile capacity of inspiratory muscles seems the main cause of AECOPD-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Indeed, the contractile capacity of the diaphragm is closely related to the length-tension relationship of the muscle. The active tension developed by the muscle during contraction is a function of the length of the muscle at rest before stimulation, which in turn is influenced by lung volume [ 55 ]. Ppl swing (i.e., DPes) following phrenic nerve stimulation decreases progressively, with increasing expiratory lung volume, by applying high levels of PEEP [ 52 , 56 , 57 ].…”
Section: How To Assist Spontaneous Breathing Across Covid-19-relatmentioning
confidence: 99%
“…Indeed, the contractile capacity of the diaphragm is closely related to the length-tension relationship of the muscle. The active tension developed by the muscle during contraction is a function of the length of the muscle at rest before stimulation, which in turn is influenced by lung volume [ 55 ]. Ppl swing (i.e., DPes) following phrenic nerve stimulation decreases progressively, with increasing expiratory lung volume, by applying high levels of PEEP [ 52 , 56 , 57 ].…”
Section: How To Assist Spontaneous Breathing Across Covid-19-relatmentioning
confidence: 99%
“…Ultrasound has been used for the assessment of diaphragm function in different clinical situations including respiratory failure requiring non-invasive ventilation. ( Cammarota et al, 2019 ; Marchioni et al, 2019 ; Ricoy et al, 2019 ) In particular the diaphragmatic thickening fraction (DTF) has been shown to correlate with pressure-generating capacity of the muscle ( Ueki et al, 1995 ), work of breathing and respiratory effort. ( Umbrello et al, 2015 ; Vivier et al, 2012 )…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated the effects of respiratory mechanics on the diaphragm function in patients with an acute exacerbation of chronic obstructive pulmonary disease (COPD) who were experiencing noninvasive ventilation (NIV) failure. 20 They stated that the ventilatory strategy and the pharmacological approach might be able to empty the lung. Therefore, the lung volume that was measured during controlled ventilation might represent static hyperinflation, but it does not correspond to the lung volume that was achieved during the spontaneous breathing trial, which is subject to dynamic hyperinflation.…”
Section: Discussionmentioning
confidence: 99%